Acoustic repertoire and calling behavior of Scinax fuscomarginatus (Anura, Hylidae) - Toledo, Luís Felipe [UNESP]; Haddad, Célio F. B. [UNESP] (Society for the Study of Amphibians and Reptiles, 2005)
Vocalizations are important in anuran communication, especially during the breeding season. Calling affects spatial organization of males at breeding sites, promotes attraction of new individuals to the chorus, and attracts mature females for reproduction. We describe four distinct vocalizations (advertisement calls, sporadic calls, and two types of aggressive calls) emitted by adult males of Scinax fuscomarginatus. With the exception of the advertisement call, the remaining descriptions are novel. We also describe calling sites, calling season, and nightly calling activity. Fieldwork was made in a fragment of Cerrado (Estação Ecológica de Itirapina), Municipalities of Itirapina and Brotas, State of São Paulo, southeastern Brazil. At this ecological station, S. fuscomarginatus exhibits a complex acoustic repertoire, social interactions and a prolonged reproductive pattern similar to observations of congeneric species at other localities. Copyright 2005 Society for the Study of Amphibians and Reptiles.
Keywords: Anura; Hylidae; Scinax